2003
DOI: 10.1007/s00592-003-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

The carnitine system and body composition

Abstract: Carnitine is a trimethylamine molecule that plays a unique role in cell energy metabolism. Mitochondrial betaoxidation of long-chain fatty acids, the major process by which fatty acids are oxidized, is ubiquitously dependent on carnitine. Control of mitochondrial beta-oxidation through carnitine adapts to differing requirements in different tissues. The physiological role of carnitine and its system in body composition is understood from insights into skeletal muscle metabolism, which converge into the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…Chitosan may act as a bile acid-sequestering agent that reduces cholesterol by interrupting enterohepatic circulation (Parra-Barraza et al, 2005). Vitamin C is essential for the synthesis of muscle carnitine (Hulse et al, 1978), a small molecule responsible for shuttling long chain fatty acids across the mitochondrial membrane for β-oxidation, subsequent fat oxidation and energy production (Siliprandi et al, 1989;Reda et al, 2003). Thus, the vitamin C status may represent a modifi able condition that might impact the expression of the obesity phenotype (Johnston, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Chitosan may act as a bile acid-sequestering agent that reduces cholesterol by interrupting enterohepatic circulation (Parra-Barraza et al, 2005). Vitamin C is essential for the synthesis of muscle carnitine (Hulse et al, 1978), a small molecule responsible for shuttling long chain fatty acids across the mitochondrial membrane for β-oxidation, subsequent fat oxidation and energy production (Siliprandi et al, 1989;Reda et al, 2003). Thus, the vitamin C status may represent a modifi able condition that might impact the expression of the obesity phenotype (Johnston, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…The main functions of L -carnitine [3-hydroxy-4-(trimethylazaniumyl)butanoate] include transferring the long-chain fatty acids through the mitochondrial barrier, the protection of membrane structures and the reduction of lactate production [8]. Lipid metabolism disorder in ischemia and anoxia can lead to accumulation of fatty acyl-CoA, which in turn may lead to membrane structure damage and cell death [9,10]. In vitro studies have shown that L -carnitine as a free radical scavenger is an effective antioxidant [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These preliminary data could have a strong clinical impact, in fact based on them: 1) patients with cancer cachexia need close monitoring of parameters of the endocrine status and of energetic and nutritional homeostasis 2) these patients require a more aggressive nutritional management to prevent malnutrition (the use of amino acids integrator contain carnitine may be recommended) [13] and then improve the qualify of life in this patients seriously ill.…”
Section: To the Editormentioning
confidence: 99%